Answer: 2cm
Step-by-step explanation:
Answer:
a) v = 12.21m/s
a = 4.07 m/s²
b)v = 11.24m/s
a = 3.75 m/s²
Step-by-step explanation:
a) Dividing the moviment into two parts:
I - With acceleration
v = v₀ + at
s = s₀ + v₀t + at²/2
- v₀ = 0
- s₀ = 0
- a = ?
- v = ?
- t = 3s
- s = x
v = v₀ + at
v = 3a ⇒ a = v/3
s = s₀ + v₀t + at²/2
x = v/3.3²/2
x = 3v/2
II - Uniform
s = s₀ + vt
s = 100
s₀ = x
v = v
t = 9.69 - 3 = 6.69s
s = s₀ + vt
100 = x + v*6.69
100 = x + 6.69v
As x = 3v/2
100 = 3v/2 + 6.69v
100 = 1.5v + 6.69v
100 = 8.19v
v = 12.21m/s
a = v/3 = 4.07 m/s²
b) Dividing the moviment into two parts:
I - With acceleration
v = v₀ + at
s = s₀ + v₀t + at²/2
- v₀ = 0
- s₀ = 0
- a = ?
- v = ?
- t = 3s
- s = x
v = v₀ + at
v = 3a ⇒ a = v/3
s = s₀ + v₀t + at²/2
x = v/3.3²/2
x = 3v/2
II - Uniform
s = s₀ + vt
s = 200
s₀ = x
v = v
t = 19.30 - 3 = 16.30s
s = s₀ + vt
200 = x + v*16.3
100 = x + 16.3v
As x = 3v/2
200 = 3v/2 + 16.3v
200 = 1.5v + 16.3v
200 = 17.8v
v = 11.24m/s
a = v/3 = 3.75 m/s²
Answer:
i think its b
Step-by-step explanation:
Constant rate means its the same rate and didn't change over time
Answer:
5(2x - 1)
Step-by-step explanation:
Given
2(x - 6) + 4(2x + 1) + 3 ← distribute both parenthesis
= 2x - 12 + 8x + 4 + 3 ← collect like terms
= (2x + 8x) + (- 12 + 4 + 3)
= 10x + (- 5)
= 10x - 5 ← factor out 5 from each term
= 5(2x - 1) ← in factored form